Construction of heparan sulfate microarray for investigating the binding of specific saccharide sequences to proteins. (16th July 2020) - Horton, Maurice; Su, Guowei; Yi, Lin; Wang, Zhangjie; Xu, Yongmei; Pagadala, Vijayakanth; Zhang, Fuming; Zaharoff, David A; Pearce, Ken; Linhardt, Robert J; Liu, Jian
Abstract: Heparan sulfate (HS) is a heterogeneous, extracellular glycan that interacts with proteins and other molecules affecting many biological processes. The specific binding motifs of HS interactions are of interest, but have not been extensively characterized. Glycan microarrays are valuable tools that can be used to probe the interactions between glycans and their ligands while relying on relatively small amounts of samples. Recently, chemoenzymatic synthesis of HS has been employed to produce specific HS structures that can otherwise be difficult to produce. In this study, a microarray of diverse chemoenzymatically synthesized HS structures was developed and HS interactions were characterized. Fluorescently labeled antithrombin III (AT) and fibroblast growth factor-2 (FGF2) were screened against 95 different HS structures under three different printing concentrations to confirm the utility of this microarray. Specific sulfation patterns were found to be important for binding to these proteins and results are consistent with previous specificity studies. Furthermore, the binding affinities (KD, surf ) of AT and FGF2 to multiple HS structures were determined using a microarray technique and is consistent with previous reports. Lastly, the 95-compound HS microarray was used to determine the distinct binding profiles for interleukin 12 and platelet factor 4. This technique is ideal for rapid expansion and will be pivotal to the high-throughput characterization of biologically important structure/function relationships.